Evaluation of an aldo-keto reductase gene signature with prognostic significance in colon cancer via activation of epithelial to mesenchymal transition and the p70S6K pathway. (6th July 2020) - Demirkol Canlı, Seçil; Seza, Esin Gülce; Sheraj, Ilir; Gömçeli, Ismail; Turhan, Nesrin; Carberry, Steven; Prehn, Jochen H M; Güre, Ali Osmay; Banerjee, Sreeparna
Abstract: AKR1B1 and AKR1B10, members of the aldo-keto reductase family of enzymes that participate in the polyol pathway of aldehyde metabolism, are aberrantly expressed in colon cancer. We previously showed that high expression of AKR1B1 (AKR1B1 HIGH ) was associated with enhanced motility, inflammation and poor clinical outcome in colon cancer patients. Using publicly available datasets and ex vivo gene expression analysis ( n = 51, Ankara cohort), we have validated our previous in silico finding that AKR1B1 HIGH was associated with worse overall survival (OS) compared with patients with low expression of AKR1B1 (AKR1B1 LOW ) samples. A combined signature of AKR1B1 HIGH and AKR1B10 LOW was significantly associated with worse recurrence-free survival (RFS) in microsatellite stable (MSS) patients and in patients with distal colon tumors as well as a higher mesenchymal signature when compared with AKR1B1 LOW /AKR1B10 HIGH tumors. When the patients were stratified according to consensus molecular subtypes (CMS), AKR1B1 HIGH /AKR1B10 LOW samples were primarily classified as CMS4 with predominantly mesenchymal characteristics while AKR1B1 LOW /AKR1B10 HIGH samples were primarily classified as CMS3 which is associated with metabolic deregulation. Reverse Phase Protein Array carried out using protein samples from the Ankara cohort indicated that AKR1B1 HIGH /AKR1B10 LOW tumors showed aberrant activation of metabolic pathways. Western blot analysis of AKR1B1 HIGH /AKR1B10 LOW colon cancer cell lines also suggested aberrant activation of nutrient-sensing pathways. Collectively, our data suggest that the AKR1B1 HIGH /AKR1B10 LOW signature may be predictive of poor prognosis, aberrant activation of metabolic pathways, and can be considered as a novel biomarker for colon cancer prognostication. Abstract : Colon tumors expressing high AKR1B1 (AKR1B1 HIGH ) and low AKR1B10 (AKR1B10 LOW ) showed worse recurrence-free survival in microsatellite stable and distal colon tumors unlike AKR1B1 LOW /AKR1B10 HIGH tumors. AKR1B1 HIGH /AKR1B10 LOW tumors were mesenchymal (CMS4); AKR1B1 LOW /AKR1B10 HIGH tumors were epithelial (CMS3) and showed activation of growth-inhibiting metabolic pathways.